2011
DOI: 10.1002/ana.22539
|View full text |Cite
|
Sign up to set email alerts
|

Trends in stroke hospitalizations and associated risk factors among children and young adults, 1995–2008

Abstract: Increases in the prevalence of ischemic stroke hospitalizations and coexisting traditional stroke risk factors and health risk behaviors were identified among acute ischemic stroke hospitalizations in young adults. Our results from national surveillance data accentuate the need for public health initiatives to reduce risk factors for stroke among adolescents and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
216
5
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 264 publications
(242 citation statements)
references
References 19 publications
16
216
5
4
Order By: Relevance
“…[7] There is growing evidence for an increase in the incidence of stroke in young adults. [8] In the present study, higher male predominance among the acute ischemic stroke in young adults was observed. Similar findings had been reported from studies conducted in western world and in India.…”
Section: Discussionsupporting
confidence: 51%
“…[7] There is growing evidence for an increase in the incidence of stroke in young adults. [8] In the present study, higher male predominance among the acute ischemic stroke in young adults was observed. Similar findings had been reported from studies conducted in western world and in India.…”
Section: Discussionsupporting
confidence: 51%
“…We found that younger patients were at relatively increased odds of stroke after ILI compared to older patients; for every decade younger age, the odds increased by almost 10%. While the absolute risk of stroke is greater in older adults, approximately 10–14% of all strokes occur in people 18–45 years old, with the incidence and prevalence of stroke in the young increasing 4, 28, 29, 30, 31, 32, 33, 34. This increasing prevalence, moreover, coupled with greater heterogeneity in stroke etiology within the younger age group than in the older stroke population, presents a unique and vulnerable patient population where risk reduction efforts are of increasing importance.…”
Section: Discussionmentioning
confidence: 99%
“…Our observed incidence rates for young strokes are similar to those in several other studies, with reported incidence rates ranging from 3 to 23 per 100 000. 9,27,28 George et al 10 have reported that ischemic stroke admissions in the United States Nationwide Inpatient Sample rose steadily from 1995 to 2008 among young adults aged 14 to 44 years, which was associated with an increase in prevalence of major risk factors such as hypertension, diabetes mellitus, and obesity. This is likely to lead to major future public health concern because stroke in younger people will influence long-term disability and result in handicap that will affect health and social care services.…”
Section: Strokementioning
confidence: 99%
“…A similar trend for stroke in young adults was also found in ischemic stroke admissions in the United States Nationwide Inpatient Sample. 10 However, most of these studies reported trends in stroke incidence in 2 or 3 different time points. 4,8,9,11 Data on continuous monitoring of stroke incidence among different ethnic groups in the same populations are lacking.…”
mentioning
confidence: 99%